Factors Influencing Student Financial Literacy (Case Study of Students at the Faculty of Economics and Government Science, Indo Global Mandiri University) - Afri Mutohar; Endah Purnamasari; Meilin Veronica (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aim to analyze the factors that affect student financial literacy with variables of class rank, GPA and pocket money. The object of this research is students of the faculty of Economics and Government Sciences, Indo Global Mandiri University. Data collection techniques were carried out by distributing questionnaires to 263 respondents individually. The hypothesis testing method is done by the chi-square test. The results of this study indicate that the class rank and GPA factors influence students’ financial literacy, while the pocket money factor do not affect students’ financial literacy.